Modeling pediatric brain tumors with human stem cells - Burket, Noah; Augustine, Titto; Tailor, Jignesh (Frontiers in Cellular Neuroscience, 2026)
With recent advances in stem cell technology, there has been an expansion of human stem and progenitor cell models of pediatric brain tumors, including use of human pluripotent and embryonic stem cells both in organoid cultures and following xenotransplantation in mice. In this review, we discuss the current approaches to modelling pediatric brain cancers using stem cells. While brain tumors describe a broad set of disease entities, we focus on glioma, medulloblastoma and ependymoma, as these are not only the most common malignant brain tumor types but also have the most stem cell models currently available. We examine human stem cell-based modeling approaches and discuss the biological questions that are being addressed using these state-of-the-art tools. Specifically, we focus on the unique advantage of using these cells to understand the functional consequences of gene mutations and their downstream growth-promoting pathways within the cell in a human context. These approaches are needed to ascertain the key players that are functionally relevant in the initiation and propagation of these tumors at the gene and protein level and to identify new drug targets. Moreover, human stem cell-based modeling approaches may complement studies in genetically engineered mouse models to address fundamental questions in tumor biology, particularly the early stages of tumorigenesis.